2016
DOI: 10.1177/1932296816663747
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Using Real-Time Continuous Glucose Monitoring (rtCGM) Data for Insulin Adjustments in Type 1 Diabetes

Abstract: The clinical benefits of real time continuous glucose monitoring (rtCGM) use have been well demonstrated in both CSII- and MDI-treated individuals in large clinical trials. However, recommendations for patient use of rtCGM in everyday life situations are lacking. This article provides guidance to clinicians and patients with type 1 diabetes (T1D) in effective use of rtCGM data, including glucose rate of change (ROC) arrows, for insulin dosing adjustments and other treatment decisions. The recommendations prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 40 publications
1
107
0
2
Order By: Relevance
“…Many CGM users had already discovered that CGM provided sufficient information, accuracy, and reliability to enable them to make insulin dosage adjustments based on CGM alone. 33,34 Effectiveness of CGM in conjunction with MDI as well as with CSII Most of the early studies with CGM were on people with type 1 diabetes who were also using an insulin pump (CSII). There have been questions as to whether similar benefits would be seen in people using basal-bolus therapy with multiple daily injections ( MDI).…”
Section: Approval For Nonadjuvant Usementioning
confidence: 99%
“…Many CGM users had already discovered that CGM provided sufficient information, accuracy, and reliability to enable them to make insulin dosage adjustments based on CGM alone. 33,34 Effectiveness of CGM in conjunction with MDI as well as with CSII Most of the early studies with CGM were on people with type 1 diabetes who were also using an insulin pump (CSII). There have been questions as to whether similar benefits would be seen in people using basal-bolus therapy with multiple daily injections ( MDI).…”
Section: Approval For Nonadjuvant Usementioning
confidence: 99%
“…Rate of change (ROC) arrows provided on the CGM display may have a greater impact than the glucose value on the need to dose insulin and in determining insulin dose amount, 7 and specific recommendations for basing treatment decisions on these ROC arrows have been published. 8 Even when CGM data were limited to adjunctive-only use, off-label use was common: in one survey, half of the CGM users indicated that they would treat a nighttime low glucose alert without a confirmatory fingerstick, and 34% indicated that they would dose insulin for hyperglycemia without SMBG confirmation. 7 A separate survey 9 revealed that 69% of Dexcom CGM users regularly use CGM alone to adjust bolus insulin doses.…”
Section: Nonadjunctive Use Of Cgmmentioning
confidence: 99%
“…They emphasized a collaborative clinician-user relationship is vital to ensure rtCGM is effective and safe in the management of diabetes. 1 We report results of our study to investigate the issues facing clinicians managing people with diabetes in terms of self-monitoring blood glucose (SMBG) with particular emphasis on providing advice on the use of ambulatory glucose profile (AGP) applied to flash glucose monitoring (FGM) in real-life clinical practice.…”
Section: Sirsmentioning
confidence: 99%